2019
DOI: 10.1182/blood-2019-123145
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab-Related Hematological Toxicities in Patients with Multiple Myeloma: A Combined Analysis of Five Phase III Randomized Controlled Trials

Abstract: Introduction: Multiple myeloma is a hematologic cancer in which clonal plasma-cell proliferation leads to complications and death. Daratumumab is a humanized IgGκ monoclonal antibody that targets CD38 with direct antitumor effects along with immunomodulatory activity, resulting in depletion of immunosuppressive cells and clonal expansion of cytotoxic T cells. Addition of daratumumab to standard multiple myeloma regimens has recently shown to improve survival in patients with multiple myeloma wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is predictable and intuitable that these types of AEs are notably influenced by the daratumumab-associated anti-myeloma agent in a certain regimen adopted. A combined analysis of five phase III randomized controlled trials showed that relative risk of all grades of neutropenia and leukopenia in patients undergoing daratumumab-based regimens was higher than that in the control arms despite lower RR of anemia ( 72 ). Finally, not properly definable as toxicity or AD, daratumumab can affect the indirect Coombs test when performed as blood group compatibility test, due to the expression of its target CD38 on red blood cells ( 73 ).…”
Section: Toxicity Profilementioning
confidence: 99%
“…It is predictable and intuitable that these types of AEs are notably influenced by the daratumumab-associated anti-myeloma agent in a certain regimen adopted. A combined analysis of five phase III randomized controlled trials showed that relative risk of all grades of neutropenia and leukopenia in patients undergoing daratumumab-based regimens was higher than that in the control arms despite lower RR of anemia ( 72 ). Finally, not properly definable as toxicity or AD, daratumumab can affect the indirect Coombs test when performed as blood group compatibility test, due to the expression of its target CD38 on red blood cells ( 73 ).…”
Section: Toxicity Profilementioning
confidence: 99%